Determinants Of Bone Mineral Density In Postmenopausal Malay Women - Rani, Sarmugam (2002)
The objective of this study was to identify factors that determine the bone mineral density (BMO) in postmenopausal Malay women. A total of 113 subjects residing in the Klang Valley participated in the study on a vol untary basis. Study subjects were healthy Malay women aged between 50 to 65 years old who had attained menopause at least 5 years at the time of the study. The BMO of total body, proximal femur, femoral neck, wards, trochanter and lumbar spine L2-L4 as well as fat mass (FM) and lean body mass (LBM) were measured using the dual energy X-ray absorptiometry (OEXA). Information on sociodemographic and reprod uctive history were collected using a questionnaire. Food intake was assessed using a three-day food record and a semiquantitative food frequency questionnaire. Physical activity was assessed using a three-day physical activity record, an open ended questionnaire and a pedometer. Knowledge, attitude and practice (KAP)